Training Needs for Early Childhood Teachers in Improving Technological, Pedagogical, and Content Knowledge Competencies - Nurillah, Salma; Herawan, Endang; Prihatin, Eka; Dikdik, Asep (EduBasic Journal: Jurnal Pendidikan Dasar, 2025)
To identify training needs for early childhood education teachers in technology integration is essential to improve learning quality. This study aims twofold: first, to analyze the training needs for early childhood education teachers in the use of technology, and second, to design a TPACK model-based training program that can assist teachers in improving the quality of learning. The present study employed a mixed methods approach, integrating both quantitative and qualitative methodologies. Data were collected through a Training Needs Survey (TNS) and subsequently analyzed utilizing SPSS. The results indicated a substantial competency discrepancy, with an average score of 39.12, falling short of the ideal score of 53. The analysis revealed that teachers continue to encounter various obstacles, including a deficiency in the development of digital teaching materials, constraints in the utilization of hardware and software, and a paucity of experience in employing interactive learning applications. These findings underscore the necessity for Technological Pedagogical Content Knowledge (TPACK)-based training to facilitate effective integration of technology in the learning process. The TPACK model enables educators not only to acquire technological mastery but also to utilize it to enhance children's interaction and engagement in the learning process. The implications offer insight for policymakers, educators, and training institutions in designing more effective training programs to improve the quality of early childhood education in the Karangpawitan Subdistrict of Garut Regency.